Observing dynamic behavioural responses due to the extension of a tram line by using panel survey - Ahmad Termida, Nursitihazlin; Susilo, Yusak O.; Franklin, Joel P. (Elsevier Ltd, 2016)
Using a four-wave panel survey of individuals’ trips and psychological attributes collected among residents along a new tram line extension in the city of Stockholm, Sweden, this study aims to investigate factors that determine the individuals’ learning and decision-making processes in using a new transport option. This includes investigating which group of travelers have used the new tram extension earlier than others, and integrated the tram extension as a part of their daily travel patterns. This paper also describes the design and construction of the four-wave panel data collection, which was collected from two weeks before and up to seven months after the opening of the new option. Descriptive analysis shows that within a seven-month period, 79% of the respondents tried the new tram exten-sion but only 14.9% of them adopted the new option as their daily travel mode. During the observed period, about 49.3% of the respondents migrated between travel modes for non-discretionary trips. Further multivariate analysis shows that middle-income travellers and travellers who owned car(s) used the new tram extension earlier than others. The effect of past experience on the current use of the tram extension on a day-to-day basis was also examined by using a mixed logit model with panel data. The purpose of the model is to examine whether individuals’ daily experiences with the new tram extension that result from repeated previous choices would affect their decisions to maintain using the new option in subsequent waves.